Defining chronic pain impact levels: a patient-clinician approach using PROMIS® pain interference scores - Karon F. Cook; Dokyoung Sophia You; Michael Von Korff; Sean C. Mackey (Journal of Patient-Reported Outcomes)
Abstract Our study aims to establish PROMIS Pain Interference score (PI) ranges that clinicians and persons living with chronic pain (PLwCP) associate with none, mild, moderate, and high impact chronic pain. We employed the PRO-Bookmarking technique to identify threshold scores that delineate different levels of chronic pain impact. PROMIS-PI score vignettes or “score stories” were developed to communicate the experience of living with different levels of pain interference. A panel of 10 PLwCP and another of 5 pain clinicians identified pairs of score vignettes they judged to represent the threshold between two levels of pain impact (e.g., ‘‘moderate impact” and ‘‘high impact”). We defined threshold scores as the mean score of the adjacent vignettes. We applied the obtained threshold scores to the distribution of PROMIS-PI scores in a sample of persons (n = 31,090) seen in a tertiary pain clinic. In another sample, we compared the Bookmarking and the revised Graded Chronic Pain Scale (GCPS-R) classifications. Patients and clinicians were in consensus on threshold scores for “no impact” to “mild impact” and “moderate impact” to “high impact,” scores of 47 and 69, respectively. However, for the threshold for “mild impact to “moderate impact,” the value was 65 for patients and 60 for clinicians. The comparison of classifications in the secondary sample revealed differences, especially for the 3rd level, high impact. The GCPS-R classified 58.2% as having high impact chronic pain; the Bookmarking thresholds classified 23.8% as such. The PRO-Bookmarking approach effectively delineated thresholds for classifying levels of chronic pain impact using PROMIS-PI scores. This method incorporates the perspectives of PLwCP and allows for post-hoc application to diverse patient samples.